Investigation of COVID-19 virus mutagenicity and the effect of the NSP13, NSP14, and NSP16 on the -1 ribosomal frameshifting - Khanifar, Ali; Najafi, Azin; Hemmati, Jaber; Nouri, Fatemeh; Hosseini, Seyed Ali; Taheri, Mohammad (Frontiers in Virology, 2024)
The COVID-19 virus is a single-stranded virus from the Coronaviridae family and has a genome of about 29881 bp, which causes acute respiratory disease. One way of transmission of the COVID-19 virus is respiratory, which is the reason for the significant transmission of the disease. The COVID-19 virus causes mutagenesis in different parts of the virus genome with its mechanisms, including -1 ribosomal frameshifting. Various parts that have undergone the most severe mutations include the spike protein, which leads to the emergence of new variants. Most of the mutations observed in the COVID-19 virus are located in the S protein and a region known as the RBD (Receptor-Binding Domain), which binds to the ACE2 (Angiotensin-converting enzyme 2) receptor in human cells. The variations in the RBD region will determine how it binds to the ACE2 receptor. Essentially, the changes created because of the mutation determine the affinity of the RBD to ACE2. On the other hand, the COVID-19 virus, because of its NSP13, NSP14, and NSP16 proteins, helps the mutation of the virus by consuming magnesium ions (Mg2+). Since the ribosome is stable with Mg2+, the COVID-19 virus, by consuming Mg2+, causes the ribosome to convert from the polysome to the monosome state, which causes a break in translation and finally leads to the formation of -1 ribosomal frameshifting.